The Zinc-Finger protein ZCCHC3 inhibits LINE-1 retrotransposition - Zhang, Zixiong; Zhang, Ning; Guo, Saisai; Liu, Qian; Wang, Shujie; Zhang, Ao; Yi, Dongrong; Zhao, Jianyuan; Li, Quanjie; Wang, Jing; Zhang, Yongxin; Ma, Ling; et al. (Frontiers in Microbiology, 2022)
Long-interspersed element 1 (LINE-1) is an autonomous non-LTR retrotransposon. Its replication can cause mutation and rearrangement of host genomic DNA, which may result in serious genetic diseases. Host cells therefore developed defense strategies to restrict LINE-1 mobilization. In this study, we reported that CCHC-type zinc-finger protein ZCCHC3 can repress LINE-1 retrotransposition, and this activity is closely related to its zinc-finger domain. Further studies show that ZCCHC3 can post-transcriptionally diminish the LINE-1 RNA level. The association of ZCCHC3 with both LINE-1 RNA and ORF1 suggests that ZCCHC3 interacts with LINE-1 RNP and consequently causes its RNA degradation. These data demonstrate collectively that ZCCHC3 contributes to the cellular control of LINE-1 replication.